RELATIONSHIP BETWEEN GROWTH AND YIELD CHARACTERS AND THEIR INFLUENCE ON YIELD OF LABLAB (LABLAB PURPUREUS L. WALP) VARIETIES GROWN AT DIFFERENT PHOSPHORUS LEVELS AND SOWING DATES IN HADEJIA JIGAWA STATE, NIGERIA - Ali, S.; Fagam, A.S.; Ringim, S.Y. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field experiment was conducted during the 2025 cropping seasons at the Binyaminu Usman Polytechnic, Hadejia Jigawa State, Nigeria to determine the relationship between growth and yield characters on yield of lablab varieties grown under different phosphorus levels and sowing dates. The treatments consisted of four levels of phosphorous (0, 20, 40 and 60 kg/ha), two local varieties of lablab (Dan Inusa and Dan Farankachi) and three sowing dates (1st, 15thand 29th of July). The experiment was laid out in a Randomized Complete Block Design (RCBD) replicated three times. Growth and yield characters were measured and correlation analysis was done. Results indicated that 60 Kg P/ha produced highest seed yield. Sowing on 29th of July had highest yield and Variety Dan Inusa out yielded the other variety. The results also showed that most of the growth and yield components had significant positive correlation with yield. However, crop growth rate was observed to have significant negative correlation with the crop yield. It could be recommended that most of the growth and yield parameters were good yield contributing characters.